2017
DOI: 10.1002/jsfa.8475
|View full text |Cite
|
Sign up to set email alerts
|

Effects of four short‐chain fatty acids or salts on fermentation characteristics and aerobic stability of alfalfa (Medicago sativa L.) silage

Abstract: BACKGROUND: The objective of the present study was to evaluate the effects of four chemicals on the fermentation quality and aerobic stability of alfalfa (Medicago sativa L.) silage. Wilted alfalfa was ensiled without additive (control), or with formic acid (FA), potassium diformate (KDF), sodium diacetate (SDA) or calcium propionate (CAP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 39 publications
3
16
0
Order By: Relevance
“…The proliferation of LAB was triggered by WSC residues and oxygen which were used by LAB as external electron acceptors to yield ATP (Kasmaei et al 2017). The transient proliferation of LAB in silage with Hex corroborated with findings of Yuan et al (2017b), who also found a slight increase in LAB populations during aerobic exposure of alfalfa treated with short-chain fatty acids (sodium diacetate and calcium propionate). The sharp decrease in LAB populations after 5 days of aerobic exposure was consistent with the depletion of WSC and the increased populations of undesirable micro-organisms.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The proliferation of LAB was triggered by WSC residues and oxygen which were used by LAB as external electron acceptors to yield ATP (Kasmaei et al 2017). The transient proliferation of LAB in silage with Hex corroborated with findings of Yuan et al (2017b), who also found a slight increase in LAB populations during aerobic exposure of alfalfa treated with short-chain fatty acids (sodium diacetate and calcium propionate). The sharp decrease in LAB populations after 5 days of aerobic exposure was consistent with the depletion of WSC and the increased populations of undesirable micro-organisms.…”
Section: Discussionsupporting
confidence: 84%
“…The ambient and silage temperatures were recorded every 30 min using a temperature logger (MDL-1048A; SMOWO Co., Ltd, Shanghai, China) until the silage was removed. The aerobic stability was considered as the number of hours that the temperature of the silage remained constant before increasing more than 2°C above the ambient temperature (Yuan et al 2017b). The silage was sampled after 3, 5 and 7 days of aerobic exposure to quantify the changes of chemical compositions and microbial populations in napier grass silage.…”
Section: Sample Preparation and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…However, to ensure that the ensiling process was performed properly, we analyzed the chemical composition of both AF and AS. The results obtained for DM (294–364 g kg −1 ) and CP (207–228 g kg −1 ) are in line with those reported previously, and confirm the dynamic pattern of fermentation and the microbial characteristics of alfalfa silage.…”
Section: Discussionsupporting
confidence: 91%
“…Hence, future research should be conducted to further examine the effects of HoLAB, HeLAB and their combinations during aerobic exposure. Although the inclusion of HeLAB on forages with a low DM content does not appear to be appropriate due to the excessive fermentation (Jatkauskas et al ., 2013), the aforementioned inoculants should be utilized so as to avoid the air deterioration that could occur during the feed out phase or due to poor management (Yuan et al ., 2018). For instance, silage moved from one silo structure to another, silage fed from intermediate feeding piles, and silos with large exposed surfaces are good candidates for treatment with HeLAB.…”
Section: Discussionmentioning
confidence: 99%